2000
DOI: 10.1029/2000jb900039
|View full text |Cite
|
Sign up to set email alerts
|

Exhumation of ultrahigh‐pressure continental crust in east central China: Late Triassic‐Early Jurassic tectonic unroofing

Abstract: Abstract. The largest tract of ultrahigh-pressure rocks, the Dabie-Hong'an area of China, was exhumed from 125 km depth by a combination of normal-sense shear from beneath the hanging wall Sino-Korean craton, southeastward thrusting onto the footwall Yangtze craton, and orogenparallel eastward extrusion. Prior to exhumation the UHP slab extended into the mantle a downdip distance of 125-200 km at its eastern end, whereas it was subducted perhaps only 20-30 km at its far western end ~200 km away. Structural rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
416
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 635 publications
(458 citation statements)
references
References 64 publications
37
416
2
3
Order By: Relevance
“…245 Ma (Early Triassic) date is considered the age of the HP event in agreement with available U/Pb and Sm/Nd ages on UHP rocks from the Dabieshan and Sulu areas (e.g. Mattauer et al, 1985;Chen et al, 1992;Ames et al, 1993;Eide et al, 1994;Hacker et al, 2000;Li et al, 1994 andJahn, 1999). These radiometric dates are consistent with stratigraphy, since south of the study area, Middle Triassic limestone is involved in the recumbent folding but Late Triassic sandstone is undeformed ( Liu et al, 2001).…”
Section: Chronological Constraintssupporting
confidence: 63%
See 1 more Smart Citation
“…245 Ma (Early Triassic) date is considered the age of the HP event in agreement with available U/Pb and Sm/Nd ages on UHP rocks from the Dabieshan and Sulu areas (e.g. Mattauer et al, 1985;Chen et al, 1992;Ames et al, 1993;Eide et al, 1994;Hacker et al, 2000;Li et al, 1994 andJahn, 1999). These radiometric dates are consistent with stratigraphy, since south of the study area, Middle Triassic limestone is involved in the recumbent folding but Late Triassic sandstone is undeformed ( Liu et al, 2001).…”
Section: Chronological Constraintssupporting
confidence: 63%
“…In the Dabieshan area, recent work recognized a main deformation phase coeval with amphibolite facies metamorphism, characterized by NW-SE trending mineral and stretching lineation associated with top-to-the-NW shearing (e.g. Hacker et al, 1995;Hacker et al, 2000 andFaure et al, 1999). Similar structures and kinematics are observed in the Sulu area Faure et al, 2003a).…”
Section: Introductionmentioning
confidence: 48%
“…However, except large metagabbro and metagranodiorite blocks, all the rocks have undergone strong ductile shear deformation and formed diverse mylonites or mylonitic rocks. Since zircon U-Pb age data obtained for the equivalent unit in the Hong'an orogen are concentrated in the Neoproterozoic, it is generally accepted that the tectonic mélange zone represents a crustal segment of the South China Block [5, [16][17][18]. Huang et al [19] obtained a muscovite 40 Ar/ 39 Ar age of 256±1 Ma in the ductile shear zone and interpreted it as the time of deformation.…”
Section: Diachroneity Of the Tongbai Hp Metamorphic Terranementioning
confidence: 99%
“…The orogen-scale structure of the axial Dabie structural belt is an antiform [53]. The north limb has north dipping foliation, north plunging lineation, and top-north shear sense formed as the footwall UHP-HP rocks were drawn southeastward out from beneath the low-grade hanging wall.…”
Section: Axial Dabie Structural Beltmentioning
confidence: 99%
“…The north limb has north dipping foliation, north plunging lineation, and top-north shear sense formed as the footwall UHP-HP rocks were drawn southeastward out from beneath the low-grade hanging wall. The south limb carries similar structures that have been rotated through horizontal to southward inclinations [53]. Based on the study in the western part of the Dabie orogen, Li et al [54] found that rocks of this orogen have been subjected to pervasive ductile deformation, and formed as asymmetric "antiform" around the core of the Xinxian UHP eclogite-facies zone.…”
Section: Axial Dabie Structural Beltmentioning
confidence: 99%